INTERACTIVE METHODS IN THE ORGANIZATION OF EDUCATION - Kholmirzayeva Mukarrama Tohirovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In this article, the formation of general education subjects at a high level among the youth of our country, achieving the specified results by using various innovative methods to ensure the quality of teaching general education subjects in this process.